Surface Immobilized Nucleic Acid–Transcription Factor Quantum Dots for Biosensing. Issue 17 (21st July 2020) - Chen, Mingfu; Nguyen, Thuy T.; Varongchayakul, Nitinun; Grazon, Chloé; Chern, Margaret; Baer, R. C.; Lecommandoux, Sébastien; Klapperich, Catherine M.; Galagan, James E.; Dennis, Allison M.; Grinstaff, Mark W.
Abstract: Immobilization of biosensors on surfaces is a key step toward development of devices for real‐world applications. Here the preparation, characterization, and evaluation of a surface‐bound transcription factor–nucleic acid complex for analyte detection as an alternative to conventional systems employing aptamers or antibodies are described. The sensor consists of a gold surface modified with thiolated Cy5 fluorophore‐labeled DNA and an allosteric transcription factor (TetR) linked to a quantum dot (QD). Upon addition of anhydrotetracycline (aTc)—the analyte—the TetR‐QDs release from the surface‐bound DNA, resulting in loss of the Förster resonance energy transfer signal. The sensor responds in a dose‐dependent manner over the relevant range of 0–200 µm aTc with a limit of detection of 80 nm . The fabrication of the sensor and the subsequent real‐time quantitative measurements establish a framework for the design of future surface‐bound, affinity‐based biosensors using allosteric transcription factors for molecular recognition. Abstract : A surface‐bound transcription factor–nucleic acid complex consists of a gold surface modified with thiolated fluorophore‐labeled DNA and an allosteric transcription factor linked to a quantum dot (QD). Upon addition of anhydrotetracycline—the analyte—the TetR‐QDs release from the surface‐bound DNA, resulting in loss of the Förster resonance energy transfer signal.